COF-CNT super-crosslinking composite hydrogel as well as preparation method and application thereof
By designing COF@CNT super crosslinked composite hydrogel, the challenges of existing seawater desalination technology to improve environmental sustainability and performance are solved, efficient photothermal conversion and water transmission are achieved, and huge potential for seawater desalination application .
Patent Information
- Application Number
- CN202411785523.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing seawater desalination technologies have challenges to environmental sustainability. Traditional membrane distillation and reverse osmosis technologies consume a large amount of fossil energy, and solar interface evaporation technology still has room for improvement in performance and application scope.
A COF@CNT supercrosslinked composite hydrogel was designed, and by chemically bonding COF to aminocarbon nanotubes and covalently crosslinking with acrylic monomer and ammonium persulfate as medium, it formed with high mechanical strength and Compound hydrogel with excellent photothermal properties.
The composite hydrogel significantly improves the photothermal conversion efficiency and water transfer rate, enhances chemical and physical stability, has huge potential for seawater desalination application, and provides new ways to environmentally friendly and sustainable technologies.
Smart Images

Figure CN119431829A_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the technical field of nanomaterials, and in particular to a COF@CNT super-crosslinked composite hydrogel and a preparation method and application thereof. Background Art
[0002] As a key means to alleviate global water shortage, seawater desalination has traditionally relied on membrane distillation and reverse osmosis technologies, but these methods are highly fossil-energy-intensive and pose a challenge to environmental sustainability. In contrast, solar interfacial evaporation technology, as an innovative way to produce fresh water, is gradually gaining attention. This technology cleverly uses solar energy as a driving force, achieves efficient photothermal conversion by designing an optimized interfacial evaporator, and concentrates light energy at the interface between water and air, thereby greatly accelerating the evaporation rate of water. Solar interfacial evaporation is not only low-cost but also highly efficient, providing potential solutions for many fields such as seawater desalination, wastewater purification, and salt recovery. Its environmentally friendly and resource-saving characteristics have made this technology a research hotspot in the scientific research community. Many researchers are working to improve its performance and expand its scope of application, in order to contribute more green and sustainable technology options to global water resource management.
[0003] At present, the composite materials of COFs and other materials (such as metal covalent organic frameworks, metal oxides and MXene, etc.) can not only make full use of the advantages of COFS materials themselves, but also effectively improve the application performance of COFs materials in the field of solar-driven photothermal desalination. Therefore, it is imperative to design COFs@CNT super-crosslinked polymer composite hydrogels with chemical and physical stability and high mechanical strength, which have great potential in seawater desalination management. Summary of the invention
[0004] In view of this, the embodiments of the present application provide a COF@CNT super-cross-linked composite hydrogel and a preparation method and application thereof. The composite material of COF and amino-modified carbon nanotubes chemically bonded to each other not only improves the light absorption capacity, but also its mesoporous channels are more conducive to the transmission of water. In addition, the COFs-based composite material with vinyl side groups not only acts as a monomer, but also acts as a cross-linking agent, thereby enhancing the chemical and physical stability and mechanical strength, and improving the photothermal performance and water transmission rate. The composite hydrogel of the present application shows great application potential in seawater desalination and is a green and sustainable development approach.
[0005] The first aspect of the embodiment of the present application provides a method for preparing a COF@CNT hyper-crosslinked composite hydrogel, comprising the following steps:
[0006] S1, dissolving a certain amount of VCOF-1@CNT in a solvent and obtaining a mixed solution by ultrasonic treatment;
[0007] S2, adding acrylic acid monomer and initiator to the mixed solution, and obtaining a precursor solution through ultrasonic treatment;
[0008] S3, heating the precursor solution to obtain a COF@CNT super-crosslinked composite hydrogel.
[0009] In some embodiments that may include the above embodiments, in step S3, the heating temperature is 80° C. and the heating time is 5 hours.
[0010] Specifically, the precursor solution was introduced into a watch glass and sealed with plastic wrap; the watch glass was placed in an oven and heated at 80° C. for 5 hours to obtain the COF@CNT super-cross-linked composite hydrogel.
[0011] In some embodiments that may include the above embodiments, in step S1, the preparation process of VCOF-1@CNT is: dissolving 1,4-divinylterephthalaldehyde and amino carbon nanotubes in a mixed solvent of o-dichlorobenzene and n-butanol, and obtaining a primary mixed solution by ultrasonic treatment; adding 1,3,5-trimethyl-2,4,6-triazine and potassium hydroxide to the primary mixed solution, and obtaining a uniform mixed solution by ultrasonic treatment; degassing the uniform mixed solution through three freeze-vacuum-thaw cycles, and flame-sealing treatment; the obtained product is washed with tetrahydrofuran, methanol, and acetone, and then dried to obtain VCOF-1@CNT.
[0012] In some embodiments that may include the above embodiments, the usage ratio of 1,4-divinylterephthalaldehyde, amino carbon nanotubes, a mixed solvent of o-dichlorobenzene and n-butanol, 1,3,5-trimethyl-2,4,6-triazine and potassium hydroxide is 28 mg:40 mg:2 mL:12 mg:16.8 mg.
[0013] In some embodiments that may include the above embodiments, the volume ratio of o-dichlorobenzene to n-butanol in the mixed solvent of o-dichlorobenzene and n-butanol is 0.6 mL:1.4 mL.
[0014] In some embodiments, which may include the above embodiments, the temperature of the flame sealing treatment is 120° C., and the time of the flame sealing treatment is 3 days.
[0015] In some embodiments that may include the above embodiments, the amount ratio of the VCOF-1@CNT, solvent, acrylic monomer and initiator is 50 mg:3.5 mL:1.5 mL:75 mg.
[0016] In some embodiments that may include the above embodiments, in step S1, the solvent is ultrapure water; in step S2, the initiator is ammonium persulfate.
[0017] Specifically, COFs material is synthesized by 1,4-divinylterephthalaldehyde and 1,3,5-trimethyl-2,4,6-triazine in a mixed solvent under the action of a catalyst; during the synthesis of COFs, amino carbon nanotubes are added to form a covalent organic framework / carbon nanotube composite material (COF@CNT) through chemical bonding; subsequently, the composite material is covalently cross-linked with acrylic acid under the action of an initiator, and finally a COF@CNT super-cross-linked composite hydrogel with a rich vinyl structure is obtained.
[0018] The second aspect of the embodiments of the present application also provides a COF@CNT hyper-cross-linked composite hydrogel prepared by the above-mentioned preparation method.
[0019] The third aspect of the embodiments of the present application also provides an application of the COF@CNT hyper-cross-linked composite hydrogel as described above in seawater desalination and pollution control.
[0020] Compared with the prior art, the embodiments of the present application have the following beneficial effects:
[0021] 1. This application uses a COF-based composite material with vinyl side groups and acrylic acid for covalent crosslinking, uses ammonium persulfate as an initiator, and prepares a hydrogel by heating, and designs a COF@CNT super-crosslinked polymer composite hydrogel with vinyl side chains;
[0022] 2. The COF@CNT super-crosslinked composite hydrogel in this application not only enhances the chemical and physical stability and mechanical strength, but also improves the photothermal performance; and the multi-level and multi-scale pores adopted are conducive to water transmission, significantly enhancing the evaporation performance of the solar steam generator; the COF@CNT super-crosslinked composite hydrogel in this application has potential important application value in the fields of seawater desalination, photocatalytic degradation of organic dyes, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0024] Figure 1 Schematic diagram of the preparation of COF@CNT super-crosslinked composite hydrogel in this application;
[0025] Figure 2 The infrared spectra of VCOF-1@CNT, acrylic acid AA and VCOF-1@CNT-Gel hydrogel in this application;
[0026] Figure 3This is a scanning electron microscope image of the VCOF-1@CNT-Gel hydrogel of this application;
[0027] Figure 4 This is a mechanical properties test diagram of VCOF-1@CNT-Gel hydrogel in this application, where Figure 4 a represents the tensile stress-strain test curve of VCOF-1@CNT-Gel hydrogel; Figure 4 b represents the angular frequency scanning curve of VCOF-1@CNT-Gel hydrogel; Figure 4 c represents the strain scanning curve of VCOF-1@CNT-Gel hydrogel;
[0028] Figure 5 The hydrophilic properties test of VCOF-1@CNT-Gel hydrogel for this application;
[0029] Figure 6 The photothermal performance test results of VCOF-1@CNT-Gel hydrogel in this application are as follows: Figure 6 a represents the photo of VCOF-1@CNT-Gel hydrogel and the infrared thermal imaging image under 1 sun; Figure 6 b represents the surface temperature distribution of VCOF-1@CNT-Gel hydrogel and VCOF-1-Gel hydrogel under single sun irradiation. DETAILED DESCRIPTION
[0030] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0031] Unless otherwise specified, the experimental methods used in the examples of this application are all conventional methods.
[0032] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.
[0033] Example 1
[0034] See attached Figure 1 The method for preparing the novel COF@CNT hyper-crosslinked polymer composite hydrogel containing vinyl and C=C conjugation in the side chain of the present application comprises the following steps:
[0035] 28 mg of 1,4-divinylterephthalaldehyde and 40 mg of amino carbon nanotubes were dissolved in a mixed solvent of 0.6 mL of o-dichlorobenzene and 1.4 mL of n-butanol, and a primary mixed solution was obtained by ultrasonic treatment; 12 mg of 1,3,5-trimethyl-2,4,6-triazine and 16.8 mg of potassium hydroxide were added to the primary mixed solution, and a uniform mixed solution was obtained by ultrasonic treatment; the uniform mixed solution was degassed through three freeze-pump-thaw cycles, flame-sealed and heated at 120°C for 3 days; the obtained product was washed and dried with tetrahydrofuran, methanol and acetone to obtain VCOF-1@CNT powder.
[0036] 50 mg of VCOF-1@CNT powder was dissolved in 3.5 mL of ultrapure water and subjected to ultrasonic treatment to obtain a mixed solution; 1.5 mL of acrylic acid and 75 mg of ammonium persulfate were added to the mixed solution and subjected to ultrasonic treatment to obtain a precursor solution; the precursor solution was introduced into a watch glass and sealed with plastic wrap; the watch glass was placed in an oven and heated at 80°C for 5 hours to obtain a COF@CNT super-cross-linked composite hydrogel, recorded as VCOF-1@CNT-Gel hydrogel.
[0037] Comparative Example 1
[0038] The preparation method of the VCOF-1-Gel hydrogel in this comparative example comprises the following steps:
[0039] 139.7 mg of 1,4-divinylterephthalaldehyde, 61.58 mg of 1,3,5-trimethyl-2,4,6-triazine and 84 mg of potassium hydroxide were added to a mixed solvent of 3 mL of o-dichlorobenzene and 7 mL of n-butanol, and a uniform mixed solution was obtained by ultrasonic treatment; the uniform mixed solution was degassed through three freeze-vacuum-thaw cycles, flame-sealed and heated at 120°C for 3 days; the obtained product was washed and dried with tetrahydrofuran, methanol and acetone to obtain VCOF-1 powder.
[0040] 50 mg of VCOF-1 powder was dissolved in 3.5 mL of ultrapure water and subjected to ultrasonic treatment to obtain a mixed solution; 1.5 mL of acrylic acid and 75 mg of ammonium persulfate were added to the mixed solution and subjected to ultrasonic treatment to obtain a precursor solution; the precursor solution was introduced into a watch glass and sealed with plastic wrap; the watch glass was placed in an oven and heated at 80°C for 5 hours to obtain a COF hyper-crosslinked hydrogel, which was recorded as VCOF-1-Gel hydrogel.
[0041] Test example
[0042] See attached Figure 2 , infrared tests were performed on VCOF-1@CNT, acrylic acid AA and VCOF-1@CNT-Gel. In the figure, VCOF-1@CNT -1The -C=C functional group at 1640 cm did not appear in VCOF-1@CNT-Gel due to its chemical reaction. -1 The strong absorption peak at comes from the C=O of the carboxyl group in PAA.
[0043] See attached Figure 3 ,Scanning electron microscopy shows that VCOF-1@CNT-Gel presents a porous structure, which is beneficial to increase the evaporation rate of seawater.
[0044] See attached Figure 4 , the mechanical properties of VCOF-1@CNT-Gel hydrogel were tested. Figure 4 a The results show that the covalently embedded COF nanoparticles act as stress buffers to dissipate energy when strain is applied, and the hydrogel has a tensile stress of 0.18 MPa (180 kPa) and an elongation of 1520%; Figure 4 b and Figure 4 c shows that the storage modulus of the hydrogel is within the tested angular frequency range (0.1-100 rad s -1 ), which confirms their hydrogel behavior. In the entire test frequency range, only slight changes in the storage modulus of the hydrogel were found, revealing a typical covalently cross-linked structure. In addition, no intersection was found between the storage modulus and loss modulus curves of the hydrogels within the test range, indicating that they exhibited a good elastic response. In the figure, G' represents the storage modulus and G" represents the loss modulus. The increase in storage modulus means that the rigidity and elasticity of the network are improved, while the increase in loss modulus means that the network has more energy dissipation during deformation, which may be related to the flexibility and dynamics of the network.
[0045] See attached Figure 5 , the hydrophilicity of VCOF-1@CNT-Gel hydrogel was tested. Figure 5 As shown, VCOF-1@CNT-Gel hydrogel exhibits great water capture ability.
[0046] See attached Figure 6 , the photothermal performance of VCOF-1@CNT-Gel hydrogel was tested. Under simulated sunlight, the surface temperature of VCOF-1@CNT-Gel hydrogel rose from 41.8℃ to above 50℃ within 17min, and the average temperature in steady state reached 55.8℃; Figure 6b It can be seen that after synthesis with CNT, the average stable temperature of the hydrogel increased significantly from 41.8°C to 53.7°C. This temperature rise clearly demonstrates the significant advantage of the VCOF-1@CNT-Gel sample in terms of photothermal conversion efficiency. In summary, the successful incorporation of CNT into VCOF-1@CNT-Gel not only greatly improves the light absorption rate of the material, but also significantly improves its photothermal conversion ability.
[0047] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a COF@CNT super-crosslinked composite hydrogel, characterized in that: The following steps are involved: S1, dissolving a certain amount of VCOF-1@CNT in a solvent and obtaining a mixed solution by ultrasonic treatment; S2, adding acrylic acid monomer and initiator to the mixed solution, and obtaining a precursor solution through ultrasonic treatment; S3, heating the precursor solution to obtain a COF@CNT super-crosslinked composite hydrogel.
2. The method for preparing the COF@CNT hyper-crosslinked composite hydrogel according to claim 1, characterized in that: In step S3, the heating temperature is 80°C and the heating time is 5 hours.
3. The method for preparing the COF@CNT hyper-crosslinked composite hydrogel according to claim 1, characterized in that: In step S1, the preparation process of VCOF-1@CNT is as follows: 1,4-divinylterephthalaldehyde and amino carbon nanotubes are dissolved in a mixed solvent of o-dichlorobenzene and n-butanol, and a primary mixed solution is obtained by ultrasonic treatment; 1,3,5-trimethyl-2,4,6-triazine and potassium hydroxide are added to the primary mixed solution, and a uniform mixed solution is obtained by ultrasonic treatment; the uniform mixed solution is degassed by three freeze-vacuum-thaw cycles, and flame-sealed; the obtained product is washed with tetrahydrofuran, methanol, and acetone, and then dried to obtain VCOF-1@CNT.
4. The method for preparing the COF@CNT hyper-crosslinked composite hydrogel according to claim 3, characterized in that: The usage ratio of the 1,4-divinylterephthalaldehyde, the amino carbon nanotubes, the mixed solvent of o-dichlorobenzene and n-butanol, 1,3,5-trimethyl-2,4,6-triazine and potassium hydroxide is 28 mg:40 mg:2 mL:12 mg:16.8 mg.
5. The method for preparing the COF@CNT super-crosslinked composite hydrogel according to claim 4, characterized in that: The volume ratio of o-dichlorobenzene to n-butanol in the mixed solvent of o-dichlorobenzene and n-butanol is 0.6 mL:1.4 mL.
6. The method for preparing the COF@CNT hyper-crosslinked composite hydrogel according to claim 3, characterized in that: The temperature of the flame sealing treatment is 120° C., and the time of the flame sealing treatment is 3 days.
7. The method for preparing the COF@CNT hyper-crosslinked composite hydrogel according to claim 1, characterized in that: The usage ratio of the VCOF-1@CNT, solvent, acrylic acid monomer and initiator is 50 mg:3.5 mL:1.5 mL:75 mg.
8. The method for preparing the COF@CNT hyper-crosslinked composite hydrogel according to claim 1, characterized in that: In step S1, the solvent is ultrapure water; in step S2, the initiator is ammonium persulfate.
9. The COF@CNT super-crosslinked composite hydrogel prepared by the preparation method according to any one of claims 1 to 8.
10. Application of the COF@CNT hyper-crosslinked composite hydrogel as claimed in claim 9 in seawater desalination and pollution control.
Citation Information
Patent Citations
Preparation method of carbon nano tube / polyacrylic acid hydrogel as well as product and application thereof
CN114031710A
Covalent organic framework nano material as well as preparation method and application thereof
CN118206771A